ASSET PRICING RESEARCH FOR BEGINNERS: SURVEY OF PROMINENT RESEARCH ON STOCK RETURNS AND RETURN DETERMINANTS (International Journal of Management, Public Policy and Research, 2024)
Over the last five decades, business academics have identified over three hundred factors that influence stock returns. A newcomer to this field might be overwhelmed by the amount of research and the nature of it - sometimes confusing, even conflicting at times. This paper tries to hand hold a beginner and gently introduce him to the high seas of asset pricing – especially research that focuses on stock returns & potential return determinants. We have tried to cover leading research that will provide a soft landing for the beginner to the field of asset pricing. With this introduction, we hope that the newcomer will find it easier to navigate her/his way confidently to her/his research interest.
Keywords: Security Analysis and Portfolio Management; Asset Pricing; Stock Returns; Stock Return Determinants; Factor Equity Investing